Large Scale Personalized Categorization of Financial Transactions - Lesner, Christopher; Ran, Alexander; Rukonic, Marko; Wang, Wei (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
A major part of financial accounting involves tracking and organizing business transactions over and over each month and hence automation of this task is of significant value to the users of accounting software. In this paper we present a large-scale recommendation system that successfully recommends company specific categories for several million small businesses in US, UK, Australia, Canada, India and France and handles billions of financial transactions each year. Our system uses machine learning to combine fragments of information from millions of users in a manner that allows us to accurately recommend user-specific Chart of Accounts categories. Accounts are handled even if named using abbreviations or in a foreign language. Transactions are handled even if a given user has never categorized a transaction like that before. The development of such a system and testing it at scale over billions of transactions is a first in the financial industry.